International and legal standards that ensure the cultural rights of a man and a citizen - Birmanova, A.I. (Bulletin of the Karaganda University “Law Series”, 2022)
The article examines the international and legal standards for ensuring and protecting the cultural rights of a man and a citizen, the implementation of which should be focused on the activities of states. The article analyzes a group of international and legal sources that declare cultural human rights of a man as the highest value of society and form the normative basis of the phenomenon. The importance of effective domestic implementation of the norms of international law in the field of protection of human rights and freedom of a man is noted. The article also pays attention to the problems of compliance with international standards for the protection of cultural human and civil rights. The ways of increasing the effectiveness of the domestic implementation of universally recognized human rights standards are outlined. The interpretation of cultural rights in various international and legal instruments and in the general comments adopted by the Committee on Economic, Social and Cultural Rights is considered. Special attention is paid to the study of the main international and legal act — the «International Covenant on Economic, Social and Cultural Rights ». The study found that significant international experience in the protection of cultural human rights has been accumulated at the present stage. The author examines in detail some problematic issues existing in the field of national and international regulation of cultural rights and freedom, analyzing the possibilities of their elimination, legal improvement and gives appropriate recommendations.